2023
DOI: 10.3389/fpsyg.2022.985847
|View full text |Cite
|
Sign up to set email alerts
|

The location of emotional intelligence measured by EQ-i in the personality and cognitive space: Are there gender differences?

Abstract: IntroductionEmotional Intelligence (EI) is first described by Salovey and Mayer as the ability to perceive and understand emotions and the ability to use them as supports for thoughts. Despite the great notoriety of EI, its definition remains not completely clear. An operative definition of EI can be achieved by studying its connection with other individual characteristics such as gender, personality traits, and fluid intelligence.MethodsThe sample was composed of 1,063 Italian subjects. A total of 330 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 89 publications
1
7
0
Order By: Relevance
“…Within the African context, data from Ethiopia draws a similar picture suggesting that female leaders scored higher in overall EI (Asmamaw and Semela, 2023). However, there is also neglected evidence showing that male participants scored higher, especially in the intrapersonal dimensions of EI (Perazzo et al, 2021;Tommasi et al, 2023). Our data provide information on leaders in the middle space offering a more detailed insight into educational leadership and gender distribution.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Within the African context, data from Ethiopia draws a similar picture suggesting that female leaders scored higher in overall EI (Asmamaw and Semela, 2023). However, there is also neglected evidence showing that male participants scored higher, especially in the intrapersonal dimensions of EI (Perazzo et al, 2021;Tommasi et al, 2023). Our data provide information on leaders in the middle space offering a more detailed insight into educational leadership and gender distribution.…”
Section: Discussionsupporting
confidence: 59%
“…Contrary to common beliefs about gender-based roles, our data surprisingly showed that-for this sample-the socially established norms do not seem stable since male participants possessed higher levels of empathy than female participants when considering the occupational role (RQ5). Research predominantly acknowledges the notion that women are more emotionally intelligent, especially in the interpersonal dimensions of EI, such as empathy (Tommasi et al, 2023). Within the African context, data from Ethiopia draws a similar picture suggesting that female leaders scored higher in overall EI (Asmamaw and Semela, 2023).…”
Section: Discussionmentioning
confidence: 99%
“… 1 It has been suggested that gender should be considered when interpreting EI scores; in particular the ability to perceive and understand others’ emotions, where women consistently achieve higher EI scores. 4 With women representing over three-quarters of the study sample, findings may reflect gender variance rather than true effects. Therefore, we suggest that the authors could have controlled for confounding factors or ensured greater gender balance.…”
Section: Dear Editormentioning
confidence: 97%
“…Factor. This study selected scale data from the formal implementation test (N = 1171, see Table 4) and used LISREL 8.80 to develop a structural equation model for confirmatory factor analysis [54] of the factor structure of the five dimensions of college counselors' professional personality.…”
Section: Analysis Of Confirmatorymentioning
confidence: 99%